A certificateless signcryption scheme for smart home networks. (13th November 2018) - Ji, Sai; Huang, Rui; Shen, Jian; Jin, Xin; Cho, Youngju
Summary: Smart home networks (SHNets) are based on the Internet of Things (IoT) and provide users with a highly intelligent home life. In recent years, SHNets have become more and more popular. In SHNets, a large amount of data interactions are needed. These data related to the privacy of users may be subject to attacks such as eavesdropping attacks, replay attacks, and mobile phone stolen attacks. Privacy protection and communication security in smart home networks have been widely studied by many scholars. However, most of the existing user authentication in current researches focus on identity‐based authentication, where the encryption protocols are divided into two steps: the signing step and the encryption step. In this paper, a certificateless signcryption scheme for SHNets is proposed which can provide biometric‐based user identity authentication. The security and performance analyses show that our scheme is efficient and secure.